2013
DOI: 10.1093/schbul/sbt155
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mirror Neuron Activity in Schizophrenia and Its Association With Theory of Mind Deficits: Evidence From a Transcranial Magnetic Stimulation Study

Abstract: Antipsychotic-naive schizophrenia patients have poorer MNA than medicated patients and healthy controls. Measures of putative MNA had significant and consistent associations with ToM abilities. These findings suggest a possibility of deficient mirror neuron system underlying SC deficits in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 59 publications
4
68
0
1
Order By: Relevance
“…In conclusion, our study supports previous evidence of poorer mnES during action observation in schizophrenia [21,22,23,24]. Moreover, it goes further by showing that emotional cues might allow patients to recover mnES, at least in part.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In conclusion, our study supports previous evidence of poorer mnES during action observation in schizophrenia [21,22,23,24]. Moreover, it goes further by showing that emotional cues might allow patients to recover mnES, at least in part.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence of poorer mnES comes from transcranial magnetic stimulation studies [21,22] and from magneto-encephalography studies [23,24]. For example, deficient motor facilitation during action observation relative to the resting state was detected in antipsychotic-naive SCZ patients as compared with medicated SCZ patients and healthy comparison subjects [22]. Accordingly, a magneto-encephalography study demonstrated that untreated SCZ patients exhibit fewer waveforms and equivalent current dipoles in the right parietal lobe than healthy subjects [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general it is probably more appropriate in humans to refer to a fronto-parietal mirror neuron system (MNS). Failure of this system has been considered important in disparate conditions including autism spectrum disorders (Hamilton, 2013), schizophrenia (Mehta et al , 2014), Alzheimer's disease and Parkinson's disease (Alegre et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…There is indeed evidence, although still preliminary, of possible underdevelopment or impairment of the mirror system in autism [12] and in those psychiatric disorders [36] in which social competence is compromised [12]. A better knowledge of the molecular and neurochemical basis of this mechanism will represent a breakthrough for establishing new therapies and interventions based on solid experimental findings.…”
mentioning
confidence: 99%